Anatomical Feasibility of Extradural Transferring S2 and S3 Ventral Roots to S1 Ventral Root for Restoring Neurogenic Bladder in Spinal Cord Injury. Issue 18 (15th September 2018) - Yang, Kaixiang; Chen, Hongtao; Tang, Jian; Ge, Dawei; Zhang, Sheng; Sui, Tao; Cao, Xiaojian
Abstract : Study Design: Anatomic study in six formalin-fixed cadavers. Objective: To determine the anatomical feasibility of transferring the S2 and S3 ventral roots (VRs) to S1 VR as a method for restoring bladder dysfunction in spinal cord injury. Summary of Background Data: A large quantity of researches of neuroanastomosis methods have been used for treating the bladder dysfunction in spinal cord injury. However, some limitations retard the development of those studies. Methods: In this study, six formalin-fixed cadavers (four males, two females) were dissected. The feasibility of exposing the S1, S2, and S3 extradural nerve roots by the limited laminectomy, isolating the VR and dorsal roots from each extradural nerve root and transferring the S2, S3 VRs to the S1 VR were assessed. The pertinent distances and the nerve cross-sectional areas in each specimen were measured. The morphology of each nerve root was observed by hematoxylin-eosin staining. Results: The limited laminectomy was performed to expose the S1 to S3 extradural nerve roots. The VRs could be isolated from each extradural nerve root at the location of the dorsal root ganglion and the hematoxylin-eosin staining showed that there were some connective tissues separating the VRs from the corresponding dorsal root ganglion. The S2 and S3 VRs have sufficient lengths to be transferred to S1 VR without grafting. The mean cross-sectional area of the S1 VR was 2.60 ± 0.17 mm 2, and that was 1.02 ± 0.32 mm 2 and 0.51 ± 0.21 mm 2 of the S2 and S3 VRs, respectively. Conclusion: This study demonstrated that use of the S2 and S3 VRs for extradural transfer to S1 VR for restoring bladder dysfunction is surgically feasible. Level of Evidence: 5